Fires in concrete structures - Significant case studies in São Paulo - Berto, Antonio Fernando (Revista ALCONPAT, 2019)
In this article, the normative aspects related to fire safety will be approached and case studies of buildings in São Paulo that suffered the fire action and its consequences will be presented. Fire safety must be considered from the conception and development of the preliminary design of the building, through the design and construction and into the operation and maintenance phase. In the design phase, the issue should be especially considered, as it establishes the basic structure of the building’s fire safety. It must be based on a thorough knowledge of the relationships with the provisions that give the building adequate levels of fire safety.